A New Hybrid Technique for Performing a Safer Bilateral Sagittal Split Osteotomy: Combining Reciprocating Saw and Piezoelectric Devices - Raffaini, Mirco; Perello, Raffaella; Conti, Marco; Hernandèz-Alfaro, Federico; Agostini, Tommaso (Facial Plastic Surgery, 2018)
The sagittal split osteotomy (SSO) is an indispensable tool in the correction of dentofacial abnormalities. In elective orthognathic surgery, it is important that surgeons inform patients about the risk of complications related to inferior alveolar nerve damage and unfavorable split. The purpose of this article is to describe a novel, hybrid technique to SSO by combining a reciprocating saw and piezoelectric devices with several advantages over traditional “pure” methods (osteotomies performed by reciprocating saw or piezoelectric devices only) in terms of precision, rapidity, easier splitting, and decreased complications related to inferior alveolar nerve damage and bad split with reduced overall morbidity. The level of evidence was Level IV, therapeutic study.
Keywords: bilateral sagittal split osteotomy; osteotomy; bone; orthognathic surgery; bimaxillary; piezosurgery